Sexual Dysfunction in Women with Type II Diabetes Mellitus - Sulastri, Rafika; Permana, Iman (JOSING: Journal of Nursing and Health, 2022)
This study aims to determine sexual dysfunction in women with type II diabetes mellitus. The research method used in this study was a literature review with database search techniques, including EBSCO, Scholar, pro-Quest, PubMed, Science Direct, and Scopus pH. After reviewing the literature, the study revealed several results of sexual disorders in women with type 2 diabetes mellitus: II, especially the factors of sexual dissatisfaction and depression. In conclusion, Based on the effect of reviews and articles, it was found that sexual dysfunction in women with type II diabetes mellitus is influenced by several elements, namely sexual satisfaction, and melancholy. Keywords: Diabetes Mellitus, Sexual Dysfunction, Women